Micropatterning of non-crystalline methylsilsesquioxane–titania hybrid films based on their structural changes with UV irradiation - Ainuddin, Ainun Rahmahwati; Hakiri, Norio; Muto, Hiroyuki; Matsuda, Atsunori (Wiley, 2012)
Non-crystalline, transparent methylsilsesquioxane–titania hybrid ﬁlms for application in micropatterning were prepared from methyltriethoxysilane and titanium tetrabutoxide by the sol–gel method. The hybrid ﬁlms were heat-treated at 100 8C for 1 h and then irradiated with UV light using an ultrahigh-pressure mercury lamp. The refractive index of the ﬁlm increased as the amount of incorporated TiO2 increased. No changes in hardness were observed for the ﬁlms lacking TiO2 during UV irradiation, whereas adding a small amount of TiO2 caused the hardness to increase signiﬁcantly following UV irradiation. These changes in the physical properties of the ﬁlms with UV irradiation were caused by the cleavage of Si–C bonds in the ﬁlms induced by the photocatalytic effect of TiO2.On the basis of the changes in surface proﬁles, and optical, chemical, and mechanical properties induced by UV irradiation, it is concluded that the methylsilsesquioxane–titania ﬁlms are promising for micropatterning by photolithography.